Fatal sclerosing mesenteritis: a 7-year-old male autopsy case report - Juan Carlos Celis Pinto,; Lucía Hernández Peláez,; Guillermo Mendoza Pacas,; Juan Mayordomo Colunga,; Milagros Balbín,; Ana Pitiot,; Héctor-Enrique Torres-Rivas,; Verónica Blanco Lorenzo, (Autopsy and Case Reports, 2023)
Sclerosing Mesenteritis (SM) is a rare diagnosis, particularly in pediatric patients, and is typically non-fatal when appropriately treated. Although molecular and immunohistochemical alterations have been described, no pathognomonic signature has been identified for this entity. This report presents a case of a seven-year-old boy who suffered sudden cardiorespiratory arrest. Upon autopsy, he was found to have multicentric SM on the upper mesentery, which led to bowel wall thinning and abdominal bleeding with bacterial translocation. We performed comprehensive morphological, immunohistochemical, and molecular analyses. SM is an atypical disorder with diverse clinical manifestations, including a rare but potentially fatal course. Early diagnosis is critical, given its potential severity. To our knowledge, this is the first case report of pediatric mortality linked to SM. Our findings emphasize the importance of increased awareness and early detection of SM in pediatric patients.